Is Antidepressant Use Associated With Difficulty Identifying Feelings? A Brief Report - Kajanoja J; Scheinin NM; Karukivi M; Karlsson L; Karlsson H. (AMER PSYCHOLOGICAL ASSOC, 2022)
Studies on the subjective effects of antidepressants suggest that they may not only improve depressed mood, but as an adverse effect also cause "emotional blunting." This phenomenon is poorly understood and little studied. The aim of this study was to examine the association of serotonergic antidepressant use and subjective emotional awareness. Emotional awareness was assessed using the Difficulty Identifying Feelings subscale from the 20-Item Toronto Alexithymia Scale. Fifty-seven individuals on antidepressant medication and 441 controls were compared. The effects of sex, age, education, as well as current depressive symptoms were controlled for. After controlling for selected variables, the antidepressant group scored higher in subjective difficulty identifying feelings, compared to controls. (p = .043, Adjusted means by Group 14.2 vs. 15.5, 95% confidence interval for mean difference between Groups 0.04-2.5). Serotonergic antidepressant use may be associated with difficulty identifying feelings. Future studies with a longitudinal setting are warranted to clarify causality.